Fotografia contemporânea brasileira: um campo expandido - Gomes, Rogério Zanetti (2016)
This study aims at investigating the current hybridity in contemporary photography in the visual arts. With its focus on Brazil, the author presents resources for a theoretical foundation of artistic photographic production and extends the study to the curatorial side of the topic. A review of literature on hybrid arts is offered on the basis of Santaella (2003), Dubois (1990), and Annateresa Fabris. A special focus is on Duchamp’s relationship with photography and art history. The concept of expanded photography is further developed with reference to Müller-Pohle (1985), Krauss (1979), Youngblood (1970), and Rubens Fernandes (2002). The study includes a report on collections of expanded photography in museums and galleries. A central part of the study is the documentation of a seminar organized by the author under the title Campo Expandido: A Convergência das Imagens (‘The Expanded Field: The Convergence of the Images’) held at Londrina State University in April 2013, in which ten speakers (artists, art critics, curators, and theorists) discussed the topic in lectures and round tables. The result of this seminar was a mapping of the field of Expanded Photography in Brazil, supporting the curatorial project ‘Brazilian Photography: Expanded Field’, presented at the end of the study